1989
DOI: 10.1002/aja.1001860305
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of pulmonary intravascular macrophages (PIMs) in ruminants: Ultrastructural and cytochemical behavior of dense surface coat

Abstract: Recent studies have indicated that pulmonary intravascular macrophages (PIMs) are a resident cell population which in structure and function resemble mature macrophages of the mononuclear phagocyte system (MPS) in various domestic species, particularly the ruminants. The ultrastructural features of PIMs of the goat and calf lungs were studied by using vascular perfusion and direct airway instillation of fixatives. Staining with tannic acid as a component of paraformaldehyde-glutaraldehydebased fixative reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 35 publications
0
30
1
Order By: Relevance
“…PIMs differentiate from monocytes in post-natal life and form firm adhesions with the capillary endothelium [15,[36][37][38]. These cells phagocytize blood-born tracer particles, bacteria and endotoxins [3,18,27,29,36]. PIMcontaining species show pulmonary hypertension following the administration of tracer particles and endotoxins, and the removal of PIMs suppresses these responses 40 O.P.…”
Section: Introductionmentioning
confidence: 99%
“…PIMs differentiate from monocytes in post-natal life and form firm adhesions with the capillary endothelium [15,[36][37][38]. These cells phagocytize blood-born tracer particles, bacteria and endotoxins [3,18,27,29,36]. PIMcontaining species show pulmonary hypertension following the administration of tracer particles and endotoxins, and the removal of PIMs suppresses these responses 40 O.P.…”
Section: Introductionmentioning
confidence: 99%
“…1). The PIMs presented their typical subcellular features particularly the globularsurface coat and a usual distribution of lysosomal particles (Atwal et al, 1989(Atwal et al, , 1992.…”
Section: Morphology Of Alveolar Septum In Untreated Controls: Ultrastmentioning
confidence: 99%
“…We have earlier suggested that TCER was most conspicuous in the adult female goat as compared to young goats of both sexes (Atwal, 1988;Atwal et al, 1990). Secondly, our purpose was to assess the effect of estrogen on the pulmonary intravascular macrophages, which are under on-going investigation in our laboratory over the last several years (Atwal et al, 1989(Atwal et al, , 1992a(Atwal et al, ,b, 1994Atwal and Minhas, 1992;Singh and Atwal, 1997). The estrogen in the past is known to cause marked changes in the number and function of cells of reticuloendothelial system which in recent years has been re-designated as Mononuclear Phagocyte System (MPS; Heller, 1957;Atwal, 1969;Loose et al, 1976;Boorman et al, 1980).…”
mentioning
confidence: 99%
“…In previous studies, we tested the hypothesis that coat was predominantly composed of lipoproteins (LDL) by using an intravenous perfusion of heparin in goats, calves, and sheep (Atwal et al, 1989;Singh et al, 1995). We also applied the conventional technique of histochemistry for LDL by in vitro digestion of lung slices in lipolytic lipase (LPL) solution.…”
mentioning
confidence: 99%
“…Both experimental procedures potentiated the disappearance of the coat from the surface and its subsequent translocation into the vacuolar system of the PIMs. These physiological and cytochemical changes were attributed to the lytic effects of LPL, mobilized from the extracellular matrix of the pulmonary endothelium and/or secreted by the PIMs (Atwal et al, 1989;Singh et al, 1995). The intracellular translocation of the coat globules was explained by assuming that LPL/LDL complexes were internalized by the PIMs upon binding to plasma membrane-associated heparin sulfate, an interaction that is heparin-sensitive under physiological conditions (Schön-herr et al, 2000).…”
mentioning
confidence: 99%